Environmental challenges and sustainable economic development in the People's Republic of China: The role of renewable energy across provinces - Sudharshan Reddy Paramati; Yukun Shi; Yang Zhao (Asian Development Bank Institute (ADBI), 2019)
In recent times, the People's Republic of China (PRC) has faced significant challenges in terms of managing its environment and moving forward with the concept of sustainable economic development. The environmental challenges concern the increasing consumption of fossil fuel energy, which has caused a substantial rise in carbon emissions. As a result, in 2015, the PRC alone contributed about 28% of the global carbon dioxide (CO2) emissions, while it contributed 17% of the global GDP. Against this backdrop, this study aims to explore empirically the impact of renewable (hydro) energy use on the economic output and carbon emissions using annual data on 28 provinces of the PRC. For this reason, the study takes yearly data from 2000 to 2014 and applies a battery of recently developed panel econometric techniques. The empirical results of augmented mean group estimations show that renewable energy has an insignificant impact on the output in all the panels. Further, the results indicate that renewable energy has a negative impact on carbon emissions in the full sample and in coastal and western provinces, but again it is insignificant. However, it contributes positively to carbon emissions in central provinces. This evidence therefore suggests that the level of renewable energy consumption has not reached a level at which it will have significant positive and negative impacts on the output and emissions, respectively.
Keywords: O44; Q42; Q48; Q56; 330; renewable energy; carbon emissions; economic output; urbanization; People's Republic of China